2017
DOI: 10.1371/journal.pntd.0005569
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mycobacterium tuberculosis-specific humoral immune responses is associated with Strongyloides stercoralis co-infection

Abstract: Background / ObjectivesHelminth infections are known to influence T cell responses in latent tuberculosis (LTBI). Whether helminth infections also modulate B cell responses in helminth-tuberculosis co-infection is not known.MethodsWe assessed Mycobacterium tuberculosis (Mtb)–antigen specific IgM and IgG levels, circulating levels of the B cell growth factors, BAFF and APRIL and the absolute numbers of the various B cell subsets in individuals with LTBI, LTBI with coincident Strongyloides stercoralis (Ss) infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…The elevation of BAFF was closely related to the Th1 immune response (17). When co-infected with Strongyloides stercoralis, BAFF and APRIL level significantly diminished in comparison to these patients with latent TB (23). In our study, we found that BAFF levels were dramatic increased in TPE patients, particularly in the pleural effusion of these patients.…”
Section: Discussionsupporting
confidence: 56%
“…The elevation of BAFF was closely related to the Th1 immune response (17). When co-infected with Strongyloides stercoralis, BAFF and APRIL level significantly diminished in comparison to these patients with latent TB (23). In our study, we found that BAFF levels were dramatic increased in TPE patients, particularly in the pleural effusion of these patients.…”
Section: Discussionsupporting
confidence: 56%
“…In another study, APRIL expression was shown to be increased in B cells of M. tuberculosis-infected patients after 6 months of anti-M. tuberculosis treatment (140). Finally, a recent study confirmed the BAFF-and APRIL-inducing effect of M. tuberculosis by measuring serum BAFF and APRIL levels in patients with latent M. tuberculosis infection (141). Although the levels of both cytokines were increased in these patients, a significant correlation was present only between BAFF and IgG levels.…”
Section: Bacteria Bacterial Infections Of the Respiratory Systemmentioning
confidence: 87%
“…The correlation between elevated BAFF levels during the acute phase of HCV infection and poor disease prognosis is a good example of this phenomenon. Furthermore, the breakage of tolerance as a consequence of chronic exposure to BAFF-inducing viruses (HIV and HCV) or parasites (T. cruzi) may be related to the preferential activation of polyreactive MZ B cells (14,141,142,168,169). Pathogens susceptible to antibody-mediated microbicidal host responses appear to prevent the development of antibody responses by downregulating the expression of BAFF and APRIL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies performed in Mtb /helminth co-infected individuals have focused on the impact of helminth infection on 1) TB diagnosis [ 27 35 ], 2) reactivation of TB from latently infected individuals (LTBI) [ 36 , 37 ] and 3) BCG vaccine immunogenicity [ 38 – 40 ]. In addition, it was recently shown that helminth infection may interfere and/or influence innate [ 41 ], cellular [ 42 44 ] and humoral [ 45 ] immune responses to Mtb . However limited information is available on the cytokine profile of Mtb -specific T-cell immune responses in subjects with Mtb /helminth co-infection.…”
Section: Introductionmentioning
confidence: 99%